Prenatal Care and Hypertensive Gestational Syndromes: A Systematic Review - Dutra, Gláucya Raquel Souza da Fonsêca; Dutra, Laio da Costa; Fonsêca, Gabriela Karine Souza da; Nascimento Júnior, Mauro Bezerra do; Lucena, Eudes Euler de Souza (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Evaluate the influence of prenatal care on the occurrence of gestational hypertension.Methods The Web of Science, Scopus, Pubmed, Cochrane and ClinicalTrials electronic databases were searched for articles published between January 1st, 2012 and December 31st, 2016. No language restrictions were imposed. The following keywords were used: prenatal care, medical assistance, prenatal education, pregnancy-induced hypertension. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) checklist was employed. Two hundred and forty articles were identified during the initial search, but only seven met the inclusion criteria. This systematic review is registered with the international prospective register of systematic reviews (PROSPERO; #CRD42017064103).Results The seven studies had a low risk of bias, with methodological quality scores ranging from six to eight points. Five studies found a positive relationship between prenatal care and pregnancy-induced hypertension, whereas two studies found no significant association between the two variables. The divergence among the studies may have been due to the type of healthcare service at which the study was conducted and the sample size.Conclusion Although the studies analyzed differed with regard to methodological aspects, the findings demonstrate the importance of prenatal care during the gestational period as a prevention and health promotion measure.
Keywords: prenatal care; medical assistance; prenatal education; hypertension pregnancy-induced; gestation